Das Gründungsgeschehen in Deutschland - Sandra Gottschalk; Hanna Hottenrott (Wirtschaftsdienst, 2024)
– The number of start-ups in Germany has been at a historically low level for a decade. While there was an annual average of 240,000 new start-ups between 1995 and 2004, the number has fallen significantly in the following years to around 165,000. One explanation is demographic change, but another is the shortage of skilled workers and labour, which makes other forms of employment attractive for potential founders. However, the significant slump in 2022 has other causes. After the turbulence of the coronavirus pandemic, the war in Ukraine led to uncertainty, which resulted in a sharp decline in the number of start-ups in many sectors. The decline in the high-tech sector is particularly noticeable. The energy sector, on the other hand, stands out due to its increasing dynamism.
Keywords: M13; 330; Unternehmensgründung; Deutschland; Unternehmensgründung; Deutschland